Ikonologia cierpienia. Aby Warburg o symbolizacji obrazowej i obrazach wojny - Pawlik, Robert (Załącznik Kulturoznawczy, 2018)
In the book Regarding the Pain of Others Susan Sontag tackles the problem of war photography as a mean of mobilization of anti war opposition. She mentions also the tradition of pictorial representations of ‘disasters of war’ as well as the western ‘iconography of suffering’. In her erudite essay, Sontag chose to omit German ‘Bildhistoriker’, Aby Warburg (1886-1929). Warburg’s concept of genesis of images from the spirit of suffering and his contribution to the study of visual aspects of war are the subjects of the present essay.